ISOLASI DAN IDENTIFIKASI SENYAWA TRITERPENOID DAN ASAM 3-HIDROKSINIKOTINAT DARI EKSTRAK DIKLOROMETANA AKAR Garcinia picrorrhiza Miq - Atiek Soemiati; Kosela S.; M. Hanafi; Leslie J. Harrison (Jurnal Kimia Terapan Indonesia, 2010)
Have been isolated chemical constituent from medicinal plants of Garcinia picrorrhiza root from Cluciaceaefamily. Two pure compounds have been isolatedfrom dichloromethane extract by flash column chromatography in silica gel and mixture of hexane and ethyl acetate (7:3) eluant (Chromatographic separation of n-hexane extract of dried G. picrorrhiza Miq. root furnished two triterpenoids, identified as Eupha-8-23-dien-7-okso-260ac acid (1) and 3-hydroxy-isonicotinic acid (2). The molecule structure of this compounds were determined based on spectrum data of measurement results FT-NMR (lD and 2D-NMR).Keyword: Cluciaceae,G. picrorrhiza, triterpen, 3-hydroxy-isonicotinic acid